Numerical Investigations of Injection Timing Effects on a Gasoline Direct Injection Engine Performance: Part A, In-Cylinder Combustion Process - Yan, Yuchao; Yang, Ruomiao; Sun, Xiaoxia; Li, Ruijie; Liu, Zhentao (Frontiers in Energy Research, 2022)
Gasoline direct injection (GDI) engine are widely adopted in the automobile industry since its advantage in the fuel economy. Injection Timing (IT) is an important parameter for the GDI engine, having a great impact on the spray atomization, mixture evenness, combustion characteristics, and therefore performance of the GDI engine. With the motive of IT optimization, a three-dimensional CFD model of a single cylinder 4-stroke spark ignition GDI engine with bore of 84 mm and compression ratio of 10.3 was utilized to analyze the detailed process at different IT (270, 280, 290, 300-degree CA BTDC), while the other conditions were invariant like rotate speed at 2000 RPM. The spray, turbulence, G-equation combustion were included. The result indicated that delayed IT tended to reduce drop-wall impingement significantly but still intensified unevenness of mixture concertation severely, resulting in fuel-rich region appeared around cylinder. Because the duration available for mixing was shortened, which dominantly intensified the unevenness of the mixture. The combustion was deteriorated as the IT delayed because the excessive equivalence ratio region severely slowed flame propagation and frozen at the most uneven region, which finally degraded thermal efficiency and engine performance. In conclusion, this paper demonstrated the whole process from injection to combustion, revealing that droplet-wall impingement and available duration for mixing are dominant trade-off factors for mixture formation and following combustion process, as the IT changes.